FEM assessment of performance of microhole textured cutting tool in dry machining of Ti-6Al-4V. Issue 9 (June 2016) - Ma, Jianfeng; Ge, Xianchen; Qiu, Changqing; Lei, Shuting
Abstract In this paper, the AdvantEdge FEM is used to investigate the performance of microhole textured cutting tools in dry three-dimensional (3D) turning of Ti alloy (Ti-6A1-4V). Microholes are designed on the rake face of cemented carbide (WC/Co) cutting inserts. The purpose is to assess the effect of microhole textured cutting tool on machining performance and to compare it with non-textured regular cutting tools. Specifically, the following microhole parameters are tested: microhole diameter, microhole depth, edge distance (the distance from cutting edge to the first line of microholes), and microhole position pattern. Their effects are assessed in terms of the cutting forces and tool-chip contact length. It is found that microhole textured cutting tools generate lower cutting force and consequently lower-energy consumption for machining. Moreover, the microhole diameter, the microhole depth, the edge distance, and the microhole position pattern all affect the cutting forces of the machining in their own way.